Telehealth use and work stress among Chinese health care providers during the COVID-19 pandemic - Shi, Jingyi; Guo, Yuqi; Yang, Fan; Kulkarni, Shanti (Decision Making and Analysis, 2023)
Telehealth services in China rapidly expanded during the COVID-19 pandemic. The work stress of health care providers (HCPs) associated with providing telehealth care services in China has been less studied. Our study describes the telehealth services provided by hospitals in China and examines the relationships between telehealth use and work stress of HCPs in China during the COVID-19 pandemic. With a survey research design, HCPs aged 18 or older in China were electronically recruited from October 19 to November 10, 2021 (n=1,073). After preprocessing, data from 1,036 HCPs were used for further analyses, which included descriptive statistics and multiple linear regression models. Results showed that 64.29% of Chinese hospitals reported virtual physician-to-physician consultations, and 59.94% of Chinese HCPs conducted online physician consultations. Lower levels of HCP work stress was associated with live video conferencing (p=0.04), online physician consultations (p=0.00), and higher levels of team collaboration (p=0.00) and team trust (p=0.00). Work stress was also positively correlated with COVID-19 stress (p=0.00), working hours (p=0.00), and the interaction between live video conferencing and COVID-19 stress (p=0.04). HCPs’ work stress decreased by using live video conferencing and online patient care. However, the positive effects of live video conferencing may decrease with the increase in COVID-19 stress for HCPs. Our findings encourage efforts to develop extensive coverage of telehealth service systems in China to promote HCPs’ virtual communication and collaboration to relieve HCPs’ work stress and support their well-being.